Mobilizing the will to prosecute: crimes of rape at the Yugoslav and Rwandan tribunals - Haddad, Heidi Nichols (Human rights review, 2011)
Widespread and systematic rape pervaded both the genocides in Bosnia–Herzegovina in 1992 and in Rwanda in 1994. In response to these conflicts, the Yugoslav Tribunal (ICTY) and the Rwandan Tribunal (ICTR) were created and charged with meting justice for crimes committed, including rape. Nevertheless, the two tribunals differ in their relative success in administering justice for crimes of rape. Addressing rape has been a consistent element of the ICTY prosecution strategy, which resulted in gender-sensitive investigative procedures, higher frequencies of rape indictments, and more successful prosecutions. In contrast, rape has not been a central focus of the ICTR prosecution strategy, which resulted in a sporadic approach to gender-sensitive investigative procedures, inconsistent rape indictments, and few successful prosecutions. What accounts for this disparity in rape prosecutions between the Rwandan and Yugoslav tribunals? Building off the existing literature that discusses factors such as legal instruments and resource capacity of the tribunal, this article argues that transnational advocacy helped generate the necessary political will to adopt and implement legal norms regarding crimes of sexual violence at the ICTY and the ICTR. Following the importance of transnational advocacy as agents of norm change, this paper also explores the antecedent conditions of advocacy mobilization that conditioned different levels of mobilization vis-à-vis the ICTY and the ICTR, including media attention and framing, connections and interest match with local groups, and geopolitical context.